The Current State of Outdoor Learning in a U.K Secondary Setting: Exploring the Benefits, Drawbacks and Recommendations - Williams, Ryan Thomas; Scott, Carla Daniella (ABC Journal of Advanced Research, 2019)
The purpose of the present study was to understand why secondary teachers are not using outdoor learning (OL) in their pedagogical practice. Through the lens of social constructivism (Vygotsky, 1986; Trowler, 2008) the research aims were to 1) examine the current benefits and drawbacks of OL, 2) distinguish factors that influence teachers’ perceptions of OL, and 3) determine, using teachers’ perceptions, if OL has a greater impact on child development than indoor learning (OL). Seven teachers were selected using purposeful sampling from a U.K secondary school. An adapted version of Fagerstam’s (2014) teachers’ perceptions questionnaire was administered to gather responses across social aspects, supporting environment, teacher-student relations, and teacher collaboration. Results from thematic analysis generated risk assessment, weather, time, flexibility, behavior, relationships, and definition as key themes. Furthermore, results showed that there is educational potential for OL, however, this does not have to be in the form of a Forest School Experience. Some teachers were in disagreement on whether the change in pupils’ behavior is perceived as positive or negative, although there were differences in year groups. The author proposes that there are educational, personal development, and fluidity factors that need to be addressed by policymakers and school leaders to encourage teachers to use the outdoor facilities more. Additionally, school leaders could use Kennedy’s (2005) award bearing model as professional development to standardize the quality of OL taking place in schools. Future research must examine the links between OL and cognitive development as much of the research in the area is through the lens of social constructivism.